Development of a mathematics learning model integrated with Bugis culture through a scientific approach - Patimbangi, Andi; Darwis, Rahma Hidayati (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purposes: The purpose of this study was to develop and test the effectiveness of a mathematics learning model integrated with Bugis culture through a scientific approach and to assess its impact on students' learning outcomes. Method: The research adopted the Research and Development (R&D) approach based on the Borg & Gall model, which involved five stages: preliminary study, planning, prototype development, product validation, and product testing. The instruments used included validation sheets, learning observations, student response questionnaires, and tests of learning outcomes. Findings: The findings revealed that the developed model was effective in improving students' mathematics learning outcomes. Additionally, the model successfully integrated Bugis cultural values into students' attitudes and behaviors. The effectiveness of the model was demonstrated by a validity and implementation rate of 85 percent and a 20 percent improvement in students' learning outcomes after the model was applied. Significance: This study highlights the significance of the model in enhancing students' academic performance while promoting local cultural values. It is recommended that the model be implemented more widely, not only to improve academic achievement but also to internalize local cultural values in students' daily lives.